PH-sensitive magnetic microcapsules for simultaneously controlled-releasing two drugs. Issue 14 (22nd September 2022) - Tang, Liwen; Yang, Ruiting; Liu, Haifang; Qin, Ziyu; Qiu, Bining; Li, Mengting; Yin, Xueqiong
Abstract: pH-sensitive magnetic dual drug-loaded microcapsules (MDDM) embracing magnetic nanoparticles Fe3 O4 @SiO2 and two drugs (roxithromycin (ROX) and theophylline (TH)) were prepared through self-assembly, with methylcellulose and alginate sodium as the wall materials. MDDM was characterized with FTIR, XRD, TGA, vibrating sample magnetometer. The amount of Fe3 O4 @SiO2 affected the drug encapsulation efficiency lightly whereas affected the diameter of MDDM obviously. The drug loading of ROX and TH was 6.44% and 7.70% at the optimized conditions, respectively. The drug releasing of MDDM expressed obvious pH-sensitivity and increased with the pH value of the medium. The total cumulative release of ROX and TH in the simulative body fluid (pH 7.4) was 83.16% and 81.86% after 12 h, while was 24.54%, 21.21% in simulative gastric liquid. MDDM had higher antibacterial activity and lower cytotoxicity than the pure drugs with same amount, showing good capability on drug protection, controlled-releasing and toxicity elimination. Graphical Abstract: UF0001